2017
DOI: 10.5821/ace.12.35.5141
|View full text |Cite
|
Sign up to set email alerts
|

Sustentabilidad y mercado: aproximaciones desde la promoción inmobiliaria

Abstract: Cómo citar este artículo: ENCINAS, F. y AGUIRRE, C. Sustentabilidad y mercado: aproximaciones desde la promoción inmobiliaria [en línea] Fecha de consulta: dd-mm-aa. En: ACE: Architecture, City and Environment = Arquitectura, Ciudad y Entorno, 12 (35): 137-164, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
3
0
3
Order By: Relevance
“…The same conclusions were drawn in the study of Eves & Kippes [32] based on surveys to home buyers in New Zealand; aspects such as location and price were the buyers' main concerns, although energy-efficiency and green housing issues appeared as major concerns for the tier of younger and older buyers in the high-income brackets. Encinas & Aguirre [33] concluded that, in the absence of mandatory energy-labels, real estate developers used marketing strategies to "green-wash" developments, which have an uncertain contribution to sustainability performance. Such "sustainable" developments attract young highly educated households.…”
Section: Brief Literature Review and Issues Around The Epbd Spanish Imentioning
confidence: 99%
“…The same conclusions were drawn in the study of Eves & Kippes [32] based on surveys to home buyers in New Zealand; aspects such as location and price were the buyers' main concerns, although energy-efficiency and green housing issues appeared as major concerns for the tier of younger and older buyers in the high-income brackets. Encinas & Aguirre [33] concluded that, in the absence of mandatory energy-labels, real estate developers used marketing strategies to "green-wash" developments, which have an uncertain contribution to sustainability performance. Such "sustainable" developments attract young highly educated households.…”
Section: Brief Literature Review and Issues Around The Epbd Spanish Imentioning
confidence: 99%
“…Finally, it is worth nothing that this unexplored topic is relevant for the Latin-American region, since Chile has become a benchmark for such region in terms of the early adoption of regulations that affect the energy 2 Santiago, as the capital city of the country, has a great importance, since it concentrates -at the same time -the 45% of the population (CChC, 2017) and 57% of the housing supply from the national real estate market (Rioseco and Tesser, 2017). It typically corresponds to a warm temperate climate with long dry season from 8 to 7 months (Csb according to the Köppen-Geiger classification), which can also be defined as a Mediterranean climate (Encinas and Aguirre, 2017). performance of dwellings.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of private or public energy-certification systems (e.g., LEED or Passivhaus) have appeared in the national market, their positioning on a general level remains incipient. For example, of all private offers published at portalinmobiliario.com, only 1.6% declared possessing such certification(Encinas and Aguirre, 2017) …”
mentioning
confidence: 99%
“…En total, se catastraron 8255 avisos publicitarios, construyendo una bases de datos, que en su análisis descriptivo y longitudinal fue publicada en Encinas & Aguirre (2017). A partir de ésta, se identificaron todos los atributos inmobiliarios contenidos en la publicidad, tanto los declarados explícitamente (por medio del texto), como los sugeridos mediante las imágenes.…”
Section: Identificación De Las Kansei Words Y Construcción De La Encuunclassified